Rapid thermal treatment robotics unit for creation of electronic equipment devices - V. A. Saladukha; V. A. Pilipenko; V. P. Yakovlev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The design specific features of the rapid thermal treatment automated unit for silicon wafers with the diameter of 100 mm are described. For preheating the unit uses the halogen lamps with a tungsten spiral of KGT 220-2000-3 in the quantity of 12 pieces, which ensure the wafer heating up to 1200 ºC with the temperature build-up rate of 10–150 ºC/s during 0.1–600 s. The annealing process is envisaged both in vacuum and in the various gaseous media. The production capacity of the unit with consideration of the wafer loading, creation of vacuum in the chamber, inflow into the chamber of the required gas, thermal treatment as per the preset program and the unloading process is ≤ 60 wafers/hour.